Comments on "Techniques and Architectures for Hazard-Free Semi-Parallel Decoding of LDPC Codes". (17th February 2010) - Gunnam, Kiran K.; Choi, Gwan S.; Yeary, Mark B.
Abstract : This is a comment article on the publication "Techniques and Architectures for Hazard-Free Semi-Parallel Decoding of LDPC Codes" Rovini et al. (2009). We mention that there has been similar work reported in the literature before, and the previous work has not been cited correctly, for example Gunnam et al. (2006, 2007). This brief note serves to clarify these issues.